A historical review of urban climatology and the atmospheres of the industrialized world. (8th August 2013) - Janković, Vladimir
Abstract : Although the scientific research in the atmospheres of urban space has been long in existence, it has still not found its proper place in the contemporary historical analysis. The historical emphasis on large‐scale phenomena and the advent of numerical weather prediction has occluded the scientific relevance and social dimension of investigations into small‐scale atmospheric processes. As a result, agricultural, forest, urban, and indoor meteorologies have received relatively little attention to date, as have micro‐climatology, turbulence studies, and the air pollution meteorology. This article provides an outline of the historical and contemporary studies of urban weather and climate in Europe and North America. It looks into the origins of the field, the evolution of main topics of research, and the processes of disciplinary institutionalization. The article suggests that a closer inspection of the developments in urban climatology would permit a more representative account of modern atmospheric sciences and provide a more comprehensive understanding of the contemporary concerns over the anthropogenic climate change. WIREs Clim Change 2013, 4:539–553. doi: 10.1002/wcc.244 This article is categorized under: Climate, History, Society, Culture > Disciplinary Perspectives